Understanding the impact of COVID-19 on the relationships and feelings of loneliness in Portuguese older adults - Fähr-Abreu, B.; Alves, R.; Neves, A. C.; Almeida, J.; Brito, I.; Justo-Henriques, S.; Bobrowicz-Campos, E. (Envelhecer com arte e a arte de envelhecer: Livro de resumos: Ageing congress2024, 2024)
The COVID-19 pandemic has shown to be harsh for the older adults, with its effects being observable on an emotional and social level. However, these effects could vary depending on the availability of formal support networks. To understand the experiences of older adults who benefitted from the institutional support, a mixed-method study was carried out, which consisted of a semi-structured interview and the completion of self-response measures (ClinicalTrials.gov ID: NCT05379426). The results presented here are partial and focus on the experiences of elders who receive home support service and frequent day-care centers. Their analysis was made within the scope of LAPSO collaboration with the ANEP’s Internship. The sample consisted of 42 women and 20 men, with an average age of 80.35 years. Participants from both groups showed similarities in terms of marital status. Progeny rates were higher in the day-care center group. Qualitative data analysis pointed to the impact of the pandemic on emotional state and on interpersonal relationships with family, peers, and caregivers. Although the availability of formal support networks was different in both groups, there were no apparent distinctions in their experiences, which were characterized by exacerbation of isolation and loneliness resulting from the implementation of contingency measures. The absence of significant differences was also verified in the quantitative data analysis, in relation to the levels of perceived social isolation and loneliness, and quality of life. This study points to the importance of formal support networks to combat isolation, highlighting the need to implement compensatory strategies in situations where access to these networks is limited, in order to prevent suffering. They also reveal the importance of continuous monitoring, both at an evaluative and interventional levels, which allows for the early detection of risk situations and timely activation of measures for preventive and protective purposes.